2022
DOI: 10.1186/s12913-022-07581-7
|View full text |Cite
|
Sign up to set email alerts
|

Access to healthcare for street sex workers in the UK: perspectives and best practice guidance from a national cross-sectional survey of frontline workers

Abstract: Background Street sex workers (SSWs) are a highly marginalised and stigmatised group who carry an extremely high burden of unmet health need. They experience multiple and interdependent health and social problems and extreme health inequality. Despite high levels of chronic physical and mental ill-health, there is little evidence of effective healthcare provision for this group. They are often considered ‘hard to reach’, but many individuals and organisations have extensive experience of workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…WES-as well as other women who have HCV-are likely to encounter barriers and stigma when accessing health care. 38,39 One strategy for reaching stigmatized communities is through peer referral. For example, a team from the University of British Columbia found that peer referrals to drug treatment were effective for WES.…”
Section: Discussionmentioning
confidence: 99%
“…WES-as well as other women who have HCV-are likely to encounter barriers and stigma when accessing health care. 38,39 One strategy for reaching stigmatized communities is through peer referral. For example, a team from the University of British Columbia found that peer referrals to drug treatment were effective for WES.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the need for services that meet the needs of sex workers, many services are not accessible or do not meet their needs (Potter et al, 2022). Often this is because sex workers anticipate stigma and lack trust in services, as well as referral to and contact from services being di cult.…”
Section: Discussionmentioning
confidence: 99%
“…Many services are inadequate for people who experience mental illness alongside substance misuse, i.e., dual diagnosis, and this inadequacy is exacerbated by the barriers that sex workers face when accessing services (Potter et al 2022). Integrated services, in community centres and hospitals, should offer information and support on both addiction and mental ill health so those in need are not passed between multiple services, as well as offering post-treatment support (National Institute of Health and Care Excellence (NICE), 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Many sex workers face large barriers to accessing health and social care. 23 There are few specialist services for this community, 24 and mainstream services are often unaware of sex working and not tailored to sex workers' needs. 17,25 Sex workers are often unaware of available services, 26 and might fear legal implications from being identified as a sex worker.…”
Section: Introductionmentioning
confidence: 99%